Autoimmune diseases: Role of steroid hormones. (October 2019) - Benagiano, Marisa; Bianchi, Paola; D'Elios, Mario Milco; Brosens, Ivo; Benagiano, Giuseppe
Abstract: Autoimmune diseases (AIDs) are a heterogeneous group of disorders in terms of clinical manifestations, pathogenesis, and prevalence, and there is no agreement to date on a common classification. Adaptive immune responses are responsible for the existence of AIDs, although innate immunity is also involved in misguiding the immune response against self-antigens. Hormones, in general, and in particular steroid hormones, play a critical role in the physiology and pathology of the immune system, especially in adaptive immunity. Hormonal factors, alone or in relation to age, sex, and reproductive status, are involved in conditioning the onset of a number of AIDs. There is a well-defined sexual dimorphism for human AIDs. At the same time, the classic view has been that steroid hormones have well-defined effects, with one type, estrogens, being "pro-inflammatory" and the other two progestogens (progesterone and its synthetic analogs) and androgens being "anti-inflammatory." Although this view has been considered too simplistic and seems contradicted by numerous observations, it remains valid: progestogens and androgens are immunosuppressive and therefore protective against AIDs, whereas estrogens are immune-stimulatory and therefore pathogenic in AIDs. Highlights: Autoimmunity is the mirror image of tolerance, reflecting the loss of tolerance. Adaptive immune responses are responsible for the existence of autoimmune diseases. Steroid hormones play a critical role in the physiology and pathology of the immune system. The view that steroid hormones have well-defined effects is too simplistic. Sex hormone action may produce different effects depending on disease risk and disease activity.